Traditional Wooden Architecture and Landscape in Karelia. Methodological considerations for the analysis and census - Parinello, Sandro; Picchio, Francesca; Porzilli, Sara (Alma Mater Studiorum, Università di Bologna, 2012)
The survey work on the Karelian landscape and traditional architecture, embedded within the European research project entitled "Wooden Architecture. Karelian Timber Traditional Architecture and Landscape", is intended to enable understanding of how Karelian culture and history have led, over time, unique urban landscapes. The context of transformation, in which they were involved in both the behavioral habits of local populations both traditional architectural ones, which are mixed with inavitabilmente models and with the administrative Soviet structures, were analyzed in this scientific field in order to not compromise the conservation and enhancement of the historic, architectural and landscape of this country. Il lavoro di indagine sul paesaggio e l'architettura tradizionale careliana, inserito all'interno del Progetto di Ricerca Europeo dal titolo "Wooden Architecture. Traditional Karelian Timber Architecture and Landscape", ha lo scopo di consentire la comprensione di come la cultura e la storia careliana abbiano determinato, nel corso del tempo, scenari paesaggistici e urbani unici nel loro genere. Il contesto di trasformazione, nel quale sono state coinvolte sia le usanze comportamentali delle popolazioni locali sia quelle architettoniche tradizionali, che si sono inavitabilmente mescolate con i modelli e con le strutture amministrative sovietiche, sono state analizzate in questo ambito scientifico al fine di non compromettere la conservazione e la valorizzazione del patrimonio storico, architettonico e paesaggistico di questo paese.